Clinical characteristics and treatment outcomes of patients with Steven-Johnson syndrome/ toxic epidermal necrolysis at Pietersburg Hospital - Rafumbedzani, Mikovhe Karyn (My University, 2025)
Background: Stevens-Johnson syndrome and toxic epidermal necrolysis (SJS/TEN) are a spectrum of a life threatening illness commonly caused by drugs. There is a paucity of studies on this condition in the country, and to the researcher’s knowledge, no study was ever conducted at Pietersburg Hospital, Limpopo Province. Objectives: To describe the clinical characteristics, evaluate management outcomes and determine associations between demographic factors and clinical characteristics of disease severity and management outcomes of patients with SJS/TEN at Pietersburg Hospital. Methods: The study was a comprehensive retrospective cross-sectional review of medical records of SJS/TEN patients, who were diagnosed by dermatologists, at Pietersburg Hospital from January 2018 to December 2022. Descriptive statistics and statistical tests were used to analyse the data. Results: The sample consisted of 43 African patients, 34.9% were male and 65.1% female, with an average age of 39±23 years. Patients with co-morbidities such as HIV, hypertension, and epilepsy accounted for 34.9% of the participants. Antibiotics and antiretrovirals drug groups commonly caused the disease, each accounting for 19% of cases. Allopurinol (14.3%) was identified as the commonest culprit, followed by trimethoprim-sulfamethoxazole (9.3%). Most patients (37.2%) had more than 30% and a SCORTEN score of 2 (34.9%). Older age was significantly associated with diabetes mellitus (p=0.003), HIV (p=0.024) and hypertension (p<0.001). Some SCORTEN parameters were significantly associated with age, which was also significantly associated with sepsis, acute renal failure and hyperkalaemia (p<0.05). The mortality rate was 13.9%, with factors such as disease severity, correlating with increased risk. Conclusion: This study provided a comprehensive review of the clinical characteristics and treatment outcomes of patients with SJS/TEN. The findings underscore the need for prompt diagnosis, identification of causative agents, and tailored therapeutic approaches to improve patient outcomes.
Thesis (M. Med. (Dermatology)) -- University of Limpopo, 2025
Keywords: Drugs; Mortality; Severe cutaneous adverse reaction; Stevens-Johnson syndrome; Toxic epidermal necrolysis; Severity-of-illness score for toxic epidermal necrolysis; Treatment outcomes (SCORTEN); Skin -- Diseases; Toxic epidermal necrolysis; Dermatology